Enhanced Performance from a Hybrid Quenchometric Deoxyribonucleic Acid (DNA) Silica Xerogel Gaseous Oxygen Sensing Platform. Issue 11 (November 2014) - Zhou, Bin; Liu, Ke; Liu, Xin; Yung, Ka Yi; Bartsch, Carrie M.; Heckman, Emily M.; Bright, Frank V.; Swihart, Mark T.; Cartwright, Alexander N.
A complex of salmon milt deoxyribonucleic acid (DNA) and the cationic surfactant cetyltrimethylammonium (CTMA) forms an organic-soluble biomaterial that can be readily incorporated within an organically modified silane-based xerogel. The photoluminescence (PL) intensity and excited-state luminescence lifetime of tris(4, 7′-diphenyl-1, 10′-phenanathroline) ruthenium(II) [(Ru(dpp)3 ] 2+, a common O2 responsive luminophore, increases in the presence of DNA-CTMA within the xerogel. The increase in the [Ru(dpp)3 ] 2+ excited-state lifetime in the presence of DNA-CTMA arises from DNA intercalation that attenuates one or more non-radiative processes, leading to an increase in the [Ru(dpp)3 ] 2+ excited-state lifetime. Prospects for the use of these materials in an oxygen sensor are demonstrated.